2010
DOI: 10.1093/hmg/ddq311
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of Dicer in adult forebrain neurons results in abnormal tau hyperphosphorylation and neurodegeneration

Abstract: Type III RNase Dicer is responsible for the maturation and function of microRNA (miRNA) molecules in the cell. It is now well-documented that Dicer and the fine-tuning of the miRNA gene network are important for neuronal integrity. However, the underlying mechanisms involved in neuronal death, particularly in the adult brain, remain poorly defined. Here we show that the absence of Dicer in the adult forebrain is accompanied by a mixed neurodegenerative phenotype. Although neuronal loss is observed in the hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
257
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(276 citation statements)
references
References 48 publications
16
257
3
Order By: Relevance
“…MiR-9 contributes to drug adaptation and adult brain plasticity by downregulating specific mRNA splice variants of this channel. 39 The potential involvement of miRNAs in age-dependent neurodegeneration is suggested by findings in conditional dicer knockout mice in which specific types of neurons are lost; [40][41][42] however, the exact mechanisms are unclear. In principle, loss of miRNAs can cause accumulation of toxic proteins and subsequent neuronal loss and might affect neuronal survival by changing the levels of trophic or prosurvival factors.…”
Section: Mir-9 In Brain Function and Neurodegenerationmentioning
confidence: 99%
“…MiR-9 contributes to drug adaptation and adult brain plasticity by downregulating specific mRNA splice variants of this channel. 39 The potential involvement of miRNAs in age-dependent neurodegeneration is suggested by findings in conditional dicer knockout mice in which specific types of neurons are lost; [40][41][42] however, the exact mechanisms are unclear. In principle, loss of miRNAs can cause accumulation of toxic proteins and subsequent neuronal loss and might affect neuronal survival by changing the levels of trophic or prosurvival factors.…”
Section: Mir-9 In Brain Function and Neurodegenerationmentioning
confidence: 99%
“…miRNAs play essential roles in NSC differentiation and the cell fate switch between neurons and glia Hebert et al, 2010;Zheng et al, 2010). We have found that Dicer-deficient NSCs display abnormal differentiation, with shorter neurites in neurons and fewer processes in glial cells (Kawase-Koga et al, 2010) (Fig.…”
Section: Cell Fate Determination Controlled By Mirnasmentioning
confidence: 93%
“…2B). Conditional deletion of Dicer from the mouse forebrain neurons using CamKII-Cre line results in neuronal degeneration and an increase in glial fibrillary acidic protein (GFAP)-positive astrocytes (Hebert et al, 2010). Dicer ablation in the dopaminoceptive neurons in the basal ganglia using a dopamine receptor-1 ( DR-1)-Cre line leads to astrogliogenesis, but not neurodegeneration .…”
Section: Cell Fate Determination Controlled By Mirnasmentioning
confidence: 99%
“…Many researchers have observed that amantadine is associated with the treatment of behavioural disturbances, synaptic and cholinergic receptors, neurotransmitter deficits and improving neurorecovery [54,55]. MiR-15a was identified as an SA-miRNA (senescence-associated miRNA) and was downregulated in AD patients' brains [56]. This miRNA is a member of the miR15/107 group, which has been implicated in neuronal degenerative diseases, including AD [57].…”
Section: Biological Insights Into Small Moleculementioning
confidence: 99%